CRIMES AGAINST CHILDREN IN AREAS OF ARMED CONFLICT: 6 THREATS ACKNOWLEDGED BY THE UN SECURITY COUNCIL - Sabina Xudaykulova (Academia Science Repository, 2023)
The pressing problem of today’s international relations in this article is the infringements faced by children in the process of protecting the rights of children in areas of armed conflict, crimes against children, especially 6 threats recognized by the UN Security Council — killing or seriously injuring children, hiring or forcibly using children as soldiers, raping or sexually abusing children, kidnapping children, school or information and analysis of crimes such as attacking a hospital, refusing humanitarian assistance to children, and their legal basis.